The mechanism of Jiuyi powder and its effective components in inhibiting the M1 phenotype polarization of macrophages on chronic and refractory wounds infected by MRSA - Yu-Lian Yin (Journal of Hainan Medical University, 2022)
Objective: To observe the effect of Jiuyi powder and its active components on the bacterial culture and macrophage phenotypic factors of the chronic refractory wound rat model, and to explore its mechanism of removing decay and promoting muscle growth. Methods: SD rats were divided into control group, Jiuyi powder group, Shengdan group, and calcined gypsum group, with 8 rats in each group. MRSA-infected skin lesions and wounds were used to build a model of chronic and difficult-to-heal wounds in rats. After the model was formed, the control group was treated with daily routine nitrofural disinfection and replaced with sterile gauze. On the basis of the control group, quantitative Jiuyi powder, Shengdan powder, and calcined gypsum powder were used for dressing change, once a day for 7 consecutive days. Before and after the last administration, collect rat wound secretions for bacterial culture, inducible monoxide nitrogen synthase content. At the same time, after the last administration, the rat wound tissue was excised for histopathology and immunofluorescence double staining to label macrophages and their M1 phenotype. Results: After the last dressing change, the wound healing of Jiuyi powder group was better than the other groups, and the wound healing rate of each group had significant difference (P <0.05). The histomology showed that the inflammation of Jiuyi powder group was controlled and had a healing trend.After the last drug change, the contents of TNF-α, IL-6 and iNOS in serum of all groups decreased, and the contents of IL-6, TNF-α and iNOS in serum of Jiuyi powder group decreased significantly before and after medication (P<0.05).There was statistical significance in serum IL-6 content between calcined gypsum group and Shengdan group before and after medication (P<0.05).In addition, the results showed that the contents of IL-6 and iNOS in serum of Jiuyi powder group were statistically different from those of the control group (P<0.05).Tissue immunofluorescence double staining showed that the positive rate of M1 macrophages in Jiuyi powder group and Shengdan group was significantly lower than that in control group (P< 0.05). The MRSA negative conversion rate of Jiuyi powder group and Shengdan group was better than that of the control group and calcined gypsum group (P<0.05). Conclusion: Jiuyi powder can improve the inflammation of chronic refractory wounds, and has antibacterial, anticorrosion and myogenic effects. Its mechanism may be related to the inhibition of macrophage M1 phenotype polarization.